WORK STRESS ON THE BAHRAINI JOURNALIST - Karim ziani, Abdul (European Scientific Journal, ESJ, 2015)
This analytical descriptive study aimed at recognizing the vocational stress that affects journalists of the Bahraini daily press, and the impacts of these stress on the journalists performing their press work effectively. The study was conducted on a sample of (230) journalists working at (AL Ayam, Al Watan, Al Wasat and Al Bilad). The study showed a low level of stress journalists faced in the Bahraini daily press. Al Watan journalists are considered the most vulnerable to pressure, compared with journalists of other press. Working conditions may be a factor in such a relatively high degree of stress in this paper as there are significant statistical differences at (0.05). Significant statistical differences also occur between all journals at (0.05), in six of the nine areas of the degree of exposure to the vocational stress in the field of press. Regarding the vocational experience variable, the only difference between journalists appeared in Al-Ayam press, which is a significant statistical difference at (0.05), while there are no statistical differences among journalists in other press as a result of vocational experience variable. The study also showed that there were no significant statistical differences between the journalists due to the variables of nationality and marital status, with the exception of Al Wasat newspaper journalists as results indicated the presence of significant differences between them. Results also indicated an increase in the proportion of fatigue among journalists of Al-Watan press (29.4). This is also true with respect to the feeling of job insecurity at the same press. The researcher recommended that an appropriate environment for the human element (the journalist) should be made available while performing responsibilities assigned to him (in the press). In this context, work stress stands as a hindrance for the journalist productivity. This requires press institutions to work hard in order to reduce it to the lowest possible degree.